Sistem Keamanan Sepeda Motor menggunakan Modul GPS Neo-7M, Selenoid Key Berbasis ESP8266 - Abdur Rohman Wakhid; Ulul Ilmi; Affan Bachri; Rifky Aisyatul Faroh; Eko Wahyu Santoso; Gilbran Bintang Erlangga (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Motorcycle theft remains a widespread issue that demands improved security solutions supported by modern technology.This research discusses the development and implementation of a motorcycle security system design using an ESP8266 microcontroller integrated incorporating the GPS Neo-7M positioning module, SW-420 vibration detection sensor, and an electronically controlled solenoid lock. The implemented mechanism is monitored and controlled via the Telegram application, allowing the owner to receive real-time updates about the motorcycle’s status through a Telegram Bot. The development process involves hardware integration, ESP8266 programming, and functional testing. The SW-420 sensor detects vibrations as indicators of possible theft, triggering a buzzer alarm and sending instant notifications through Telegram. The GPS Neo-7M module provides location data in real time, automatically or upon user request, through a Google Maps link. Users can also lock or unlock the motorcycle remotely by sending the lock or /unlock commands via Telegram. Test results show that the system responds to vibrations in less than one second, delivers Telegram notifications within 3–5 seconds, and determines location with an accuracy of 3–10 meters. Overall, the proposed system offers an effective, practical, and low-cost solution to enhance motorcycle security.